Role of miR-944/MMP10/AXL- axis in lymph node metastasis in tongue cancer - Bhasker Dharavath; Ashwin Butle; Ankita Pal; Sanket Desai; Pawan Upadhyay; Aishwarya Rane; Risha Khandelwal; Sujith Manavalan; Rahul Thorat; Kavita Sonawane; Richa Vaish; Poonam Gera; et al. (Communications Biology, 2023)
MMP10, which is upregulated in 86% of primary tongue tumors with lymph node metastases, is negatively regulated by miR-944 and promotes nodal metastasis in an orthotopic tongue cancer mouse model through the AXL signaling pathway.